More than Words: Strategies Used by Indonesian Tourist Guides to Interpret Cultural Terms in Surakarta and Yogyakarta Royal Palaces - Purnomo, Budi (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Interpretation of cultural terms meaning between spoken languages is not often simply a word to word transference from a source language into a target language. This research is intended to investigate the strategies used by Indonesian tourist guides to interpret cultural terms during providing assistance and information to English speaking tourists visiting four royal palaces in Surakarta and Yogyakarta cities. This study is of a qualitative and descriptive nature. The data were collected through joining twenty guided group tours in Kasunanan Palace, Mangkunegaran Palace (Surakarta City), Kasultanan Palace and Pakualaman Palace (Yogyakarta City) and recording the tourist guides interpretation of cultural terms to tourists. The cultural terms were classified into five categories: palace properties, royal heirlooms, ancient weapons, precious antiques and cultural ceremonies. The research findings show that the interpretation strategies used by tourist guides to interpret cultural terms are: addition, borrowing, cultural equivalent, descriptive equivalent and componential analysis. The findings indicate strongly that the Indonesian tourist guides should improve their interpretation skills in order that their guiding services become more meaningful, especially to overcome cultural obstacles.